PERENCANAAN PRODUKSI UNTUK MEMENUHI PERMINTAAN DENGAN BIAYA YANG OPTIMAL - Sawargo, Andre Leonard; Mundari, Siti (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2014)
The final task is to give consideration to the company to add crumble pellet machine in an effort to increase production so as to meet the demand. In completing this final project used several techniques to compare the economic methods addition of new machines, and production planning.Worth Annual method to determine the annual value of an investment and summed with the cost of production and comparability with the cost of production without new investment. HoltWinter forecasting method to forecast the demand for 1 year. And after that calculates the cost of production when using the addition crumble pellet machine and do not use the machine additions crumble pellets. Smaller production costs are selected.